Fundamentals of physics. - Walker, Jearl, 1945- (Hoboken : Wiley, 2008)
PART 1 Measurement Motion Along a Straight Line Vectors Motion in Two and Three Dimensions Force and Motion I Force and Motion II Kinetic Energy and Work Potential Energy and Conservation of Energy Center of Mass and Linear Momentum Rotation Rolling Torque, and Angular Momentum PART 2 Equilibrium and Elasticity Gravitation Fluids Oscillations Waves I Waves II Temperature, Heat, and the First Law of Thermodynamics The Kinetic Theory of Gases Entropy and the Second Law of Thermodynamics PART 3 Electric Charge Electric Fields Gauss? Law Electric Potential Capacitance Current and Resistance Circuits Magnetic Fields Magnetic Fields Due to Currents Induction and Inductance Electromagnetic Oscillations and Alternating Current Maxwell?s Equations; Magnetism of Matter PART 4 Electromagnetic Waves Images Interference Diffraction Relativity PART 5 Photons and Matter Waves More About Matter Waves All About Atoms Conduction of Electricity in Solids Nuclear Physics Energy from the Nucleus Quarks, Leptons, and the Big Bang